A Longitudinal Study of Adherence to the Mediterranean Dietary Pattern and Metabolic Syndrome in a Non-Mediterranean Population - Mirmiran, Parvin (Int J Endocrinol Metab, 2015)
BACKGROUND: Adherence to the Mediterranean diet (MedDiet) has been proposed to reduce the risk of metabolic syndrome (MetS), but the association of the diet on MetS in non-Mediterranean populations remains unclear. OBJECTIVES: The aim of this study was to investigate whether adherence to the MedDiet is related to the incident MetS and its components during a 3-year follow-up among Iranian adults. PATIENTS AND METHODS: Longitudinal associations between the MedDiet and MetS components were investigated on 2241 adults, aged 18 - 74 years, without type 2 diabetes selected from participants of the Tehran lipid and glucose study (TLGS). The association between the MedDiet and MetS incidence was also examined in 1661 participants, free of Mets at baseline. Adherence to the MedDiet was assessed using the traditional Mediterranean diet score (MDS) and a recently posteriori adaptation of the MDS of Sofi et al. (Sofi-MDS). MetS was defined according to the recent interim consensus. RESULTS: After adjusting for potential confounders, neither higher MDS nor higher Sofi-MDS were significantly associated with the mean values of MetS components and the risk of metabolic abnormalities incidence after 3 years follow-up. During the 3 years of follow-up, 246 developed MetS were identified. In multivariable model, the adjusted odds ratio (OR) of developing MetS did not differ significantly in participants with the highest tertile of the MDS (OR (95% CI): 0.88 (0.62 - 1.23)) or sofi-MDS (OR (95% CI):1.12 (0.77 - 1.62)) compared to those in the lowest tertiles. CONCLUSIONS: Adherence to the MedDiet, according to MDS and Sofi-MDS, may not predict MetS components and MetS incidence after 3 years of follow-up in Iranian adult populations.